Adjustment Trajectories in College Science Programs: Perceptions of Qualities of Parents' and College Teachers' Relationships. - Duchesne, Stéphane; Ratelle, Catherine F.; Larose, Simon (Journal of Counseling Psychology, 2007)
This longitudinal study had 2 goals. The 1st goal was to describe trajectories of academic and emotional adjustment in college science programs. The 2nd goal was to determine whether these trajectories differed as a function of students' self-reports of the quality of their relationships with parents and teachers. The sample consisted of 498 students recruited during their last year of high school. Assessment of adjustment continued until the end of the 2nd year of college. For a number of students, the authors observed a significant decline in both academic and emotional adjustment. Moreover, it was possible to identify an at-risk profile characterized by poor academic and emotional adjustment. In examining the students' perceptions of their family and school environments, the authors found that poorly and well-adjusted students differed from each other on the basis of parental but not teachers' relationship quality. Reprinted by permission of the publisher.